2016
DOI: 10.1002/pmic.201500405
|View full text |Cite
|
Sign up to set email alerts
|

Screening for potential serum biomarkers in rat mesangial proliferative nephritis

Abstract: Mesangial proliferative nephritis (MesPGN) is a common kidney disease worldwide. The main feature of the disease is mesangial cell proliferation-induced injury to kidney function. In this study, we explored serum biomarkers for kidney function injury in anti-Thy1 nephritis. We found that mesangial proliferation were increased on days 5 and 7, and recovered by day 14 in anti-Thy1 nephritis. 24-h urine protein, the ratio of urine protein to urine creatine, serum creatine, and blood urea nitrogen, were increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Consistent with the molecular function evidence, the 21 restored proteins were significantly enriched in the biological processes of "negative regulation of endopeptidase activity" (p 0.0002, 4 proteins), "negative regulation of peptidase activity" (p 0.0002, 4 proteins), "regulation of endopeptidase activity" (p 0.001, 4 proteins), and "response to estradiol" (p 0.049, 3 proteins) (Figure 2D and Supplementary Tables S3). Notably, 13 of the 21 proteins had been previously identified as kidney disease markers, including Ambp, alanyl aminopeptidase (Anpep), B2m, C3, Camp, Cdh1, Col1a1, gammaglutamyltransferase 1 (Ggt1), Myh6, Plau, Ptgds, Slc3a1, and Tff1 (Dussol et al, 2004;Arumugam et al, 2007;Ryu et al, 2007;Humphreys et al, 2008;Holliday et al, 2010;Chen, 2011;Roberts et al, 2014;Jia et al, 2015;Menon et al, 2015;Lu et al, 2016;Flyvbjerg, 2017;Hayek et al, 2017;Ix et al, 2017;Jerebtsova et al, 2017;Rubinow et al, 2017;Wei et al, 2017).…”
Section: Hpl Administration Restores the Ovx-induced Abnormal Fluctuations In The Renal Proteomic Profilementioning
confidence: 99%
“…Consistent with the molecular function evidence, the 21 restored proteins were significantly enriched in the biological processes of "negative regulation of endopeptidase activity" (p 0.0002, 4 proteins), "negative regulation of peptidase activity" (p 0.0002, 4 proteins), "regulation of endopeptidase activity" (p 0.001, 4 proteins), and "response to estradiol" (p 0.049, 3 proteins) (Figure 2D and Supplementary Tables S3). Notably, 13 of the 21 proteins had been previously identified as kidney disease markers, including Ambp, alanyl aminopeptidase (Anpep), B2m, C3, Camp, Cdh1, Col1a1, gammaglutamyltransferase 1 (Ggt1), Myh6, Plau, Ptgds, Slc3a1, and Tff1 (Dussol et al, 2004;Arumugam et al, 2007;Ryu et al, 2007;Humphreys et al, 2008;Holliday et al, 2010;Chen, 2011;Roberts et al, 2014;Jia et al, 2015;Menon et al, 2015;Lu et al, 2016;Flyvbjerg, 2017;Hayek et al, 2017;Ix et al, 2017;Jerebtsova et al, 2017;Rubinow et al, 2017;Wei et al, 2017).…”
Section: Hpl Administration Restores the Ovx-induced Abnormal Fluctuations In The Renal Proteomic Profilementioning
confidence: 99%
“…A previous study screening a blood transcriptome-based molecular signature demonstrated that VNN3 may serve as a more specific and sensitive diagnostic biomarker for ST-segment-elevation myocardial infarction than traditional creatine kinase-MB or troponin ( 29 ). Additionally, the expression of VNN3 was also found to be upregulated in mesangial proliferative nephritis and skin psoriasis lesions, suggesting its proinflammatory activity in diseases ( 30 , 31 ). Collectively, the findings of the present study may hint at the potential for SLC22A4, IL1R2 and VNN3 associated with altered NLR to predict the prognosis with CHF patients owing to their evidenced biological properties in cardiovascular and inflammatory diseases to some extent.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, the current study also disclosed that serum ITIH4 at any time point declined in sepsis deaths compared to survivors. The potential reasons would be that: (1) ITIH4 exerted an anti‐inflammatory effect; thus, its decrease could reflect aggravated inflammation 13,14 ; (2) ITIH4 involved in the pathology of multiorgan function and its reduction might represent anabatic lung and kidney injury 33–35 . Notably, inflammation and multiorgan injuries were worse in sepsis deaths compared with survivors 37 ; thus, serum ITIH4 at any time point was reduced in deaths in contrast to survivors.…”
Section: Discussionmentioning
confidence: 99%
“…It was discovered that serum ITIH4 was inversely related to lung injury, renal injury, and disease severity. The potential explanations would be that: (1) ITIH4 could inhibit alveolar epithelial cell apoptosis and senescence, thus reducing respiratory injury 33 , 34 ; (2) ITIH4 might also suppress the mesangial cell proliferation to relieve renal injury 35 ; (3) as discussed above, ITIH4 could reflect favorable clinical features, attenuated inflammation, and relieved organ injury; therefore, it might also represent decreased disease severity to a certain extent. Taken together, serum ITIH4 was negatively correlated with lung and renal injury, along with disease severity in sepsis patients.…”
Section: Discussionmentioning
confidence: 99%